The Influence of Salary and Incentives on the Performance of State Civil Apparatus in the Regional Education Office of North Sulawesi Province - Usman, Okthariane Lidya; Bogar, Wilson; Kairupan, Sisca B.; Mandagi, Marthinus (Technium Social Sciences Journal, 2025)
This study aimed to 1) determine the effect of salary (X1) on State Civil Apparatus (ASN) performance (Y), 2) determine the effect of incentives (X2) on ASN performance (Y), 3) determine the effect of salary (X1) and incentives (X2) together on ASN performance (Y) at the Regional Education Office of North Sulawesi Province. The research method used is quantitative research method. The number of samples was 87 state civil apparatus (ASN). The data analysis technique used multiple linear analysis models. The results showed that 1) Salary has a positive and significant effect on ASN performance at the Regional Education Office of North Sulawesi Province. This can be shown by the regression equation Ŷ = 6.514 + 0.765 X₁, then the hypothesis H1 is accepted and H0 is rejected. From these results, it means that the higher the salary, the higher the ASN performance. 2) Incentives have a positive and significant effect on ASN performance at the Regional Education Office of North Sulawesi Province. This can be shown by the regression equation Ŷ = 6.514 + 0.239 X₂, then hypothesis H1 is accepted. From these results, it means that the higher the incentive, the higher the ASN performance. 3) Salary and incentives together (simultaneously) have a positive and significant effect on ASN performance at the Regional Education Office of North Sulawesi Province. This is indicated by the Fcount value of 4.16 with the regression equation Ŷ = 6.514 + 0.765 X₁ + 0.239 X₂, then hypothesis H1 is accepted. From these results, it means that the higher the salary and incentives, the higher the ASN performance.